A study of total mesorectal excision for rectal cancer-upfront and after neoadjuvant chemotherapy or chemoradiation - Bijyal, Sajan; Rajra, Avinash; Chauhan, Virta (International Surgery Journal, 2022)
Background: Colorectal cancer is a major cause of morbidity and mortality throughout the world. The incidence of rectal carcinoma is increasing in developing countries. Challenge in preoperative evaluation remains to identify patients who might benefit from neoadjuvant chemotherapy or chemoradiation (NACT/RT). The aim of this study was to study the correlation of final histopathology specimen (pathological tumor regression grade) with preoperative MRI (magnetic resonance tumor regression grade) (mrTRG). Method: This was a prospective observational analysis with operable rectal cancer of mid or distal rectum who underwent total mesorectal excision either upfront or following CT/RT. Preoperative MRI was done for local staging and also to assess response to neo-adjuvant CT/RT. Histo-pathological specimen was assessed for pathological tumor regression and correlation between mrTRG and pathological tumor regression grading (pTRG) analysed. Results: Out of 79 patients, 69 patients received NACRT and 10 patients underwent upfront surgery. On bivariate analysis mrTRG and pTRG corresponded in 47 patients whereas in 22 patients it didn’t correspond. There was a statistically significant agreement between mrTRG and pTRG (p=0.0491). Conclusions: mrTRG grading was identified as a reliable predictor of pathological response after neoadjuvant chemoradiotherapy and thus a predictor of completeness of resection. So, efforts should be routinely done to do a mrTRG grading as it not only provides oncological safety but also reduces post operative mortality.